High-water-absorption chenille floor mat and production process thereof
By woven the Chenille yarn, polyester monofilament and modified fibers into yarns and soaking them in the zinc sulfate hexahydrate aqueous solution, combined with the photocatalytic sterilization effect of the modified filler, the Chenille floor mat has poor water absorption and easy bacterial breeding, and the effect of high water absorption, stain resistance and antibacteriality is achieved.
Patent Information
- Application Number
- CN202510149647.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-11
AI Technical Summary
At this stage, Chenille floor mats are average in water absorption and are prone to hiding dirty and breeding bacteria.
The highly absorbent Chenille floor mat was made by woven chewed yarn, polyester monofilament and modified fibers into yarn, and woven into tulle looms, soaked in an aqueous zinc sulfate hexahydrate solution, combined with the photocatalytic bactericidal effect of the modified filler, a highly absorbent Chenille floor mat was made.
The water absorption and stain resistance of Chenille floor mats are significantly improved. At the same time, the antibacterial properties of the floor mats are enhanced through the photocatalytic action of the modified filler and avoid bacterial growth.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chenille mat preparation, and in particular to a high water-absorbent chenille mat and a production process thereof. Background Art
[0002] Chenille yarn is a new type of fancy yarn, which is made of two strands of yarn as the core, and twisted to sandwich the feather yarn in the middle. Textiles made of chenille yarn as the main raw material have the characteristics of full fiber, thick fabric and light texture, high skin-friendliness and exquisite appearance. They are widely used in home textiles and knitted clothing, such as chenille mats. However, due to the special structure of chenille yarn, chenille mats are very easy to hide dirt. It is not easy to completely dry the adjacent feathers during washing and drying, and it is easy to breed bacteria after long-term use. Summary of the invention
[0003] The purpose of the present invention is to provide a high water-absorbent chenille floor mat and a production process thereof, so as to solve the problem that the water absorption of the current chenille floor mat is average and it is easy to harbor dirt and breed bacteria.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A production process of a highly absorbent chenille floor mat, comprising the following steps: Chenille yarn, polyester monofilament and modified fiber are woven into yarn to obtain woven yarn, which is woven into chenille base cloth through a tufting loom, and the chenille base cloth is soaked in a hexahydrate zinc sulfate aqueous solution at a temperature of 50-60°C for 6-8 hours, taken out and dried, and then dyed, sorted, repaired and re-bottomed to obtain a highly absorbent chenille floor mat.
[0005] The single yarn quantity ratio of the chenille yarn, the polyester monofilament and the modified fiber is 4:1:2.
[0006] Further, the modified fiber is prepared by the following steps: Step A1: Acryloyl chloride, p-hydroxybenzaldehyde, triethylamine and DMF are mixed, and reacted for 2-3 hours at a speed of 150-200 r / min and a temperature of 25-30° C. to obtain intermediate 1; intermediate 1, o-phenylenediamine, potassium carbonate and anhydrous ethanol are uniformly mixed, and refluxed for 10-15 hours at a speed of 150-200 r / min and a temperature of 78-80° C., and the pH value is adjusted to 5-5.5 to obtain a modified monomer; Step A2: dissolving sodium carboxymethyl cellulose in deionized water, adding sodium hydroxide solution, stirring and adding acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF at a speed of 120-150 r / min, a temperature of 70-75° C. and nitrogen protection, stirring for 10-15 minutes, adding potassium persulfate, and reacting for 6-8 hours to obtain a polymer solution; Step A3: The polymer solution and the modified filler are mixed evenly to obtain a spinning solution, and electrospinning is performed at a voltage of 20-25 kV, a spacing of 20-25 cm, and a speed of 1.5 mL / h to obtain modified fibers.
[0007] Furthermore, the usage ratio of acryloyl chloride, p-hydroxybenzaldehyde and triethylamine in step A1 is 1:1:1.1, and the molar ratio of intermediate 1, o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0008] Furthermore, the amount ratio of sodium carboxymethyl cellulose, deionized water, sodium hydroxide solution, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF described in step A2 is 4.5g:50mL:20mL:20g:8g:15g:60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount of potassium persulfate is 1% by mass of acrylic acid.
[0009] Furthermore, the usage ratio of the polymer solution and the modified filler in step A3 is 200 mL: 1-5 g.
[0010] Further, the modified filler is prepared by the following steps: Step B1: dispersing graphene oxide in anhydrous ethanol, stirring and adding γ-aminopropyltriethoxysilane and dicyclohexylcarbodiimide at a speed of 120-150 r / min and a temperature of 40-50° C., and reacting for 3-5 hours to obtain pretreated graphene; Step B2: The pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and anhydrous ethanol are mixed evenly, stirred and deionized water and hydrochloric acid solution are added at a speed of 60-80r / min and a temperature of 65-70°C, and the reaction is carried out for 2-3h. Then, tetrabutyl titanate is added and the reaction is continued for 3-5h. The temperature is raised to 120-130°C and kept warm for 1-1.5h to obtain a precursor. The precursor is added into a muffle furnace and calcined for 2-3h at a temperature of 500-550°C in a nitrogen protection atmosphere to obtain a modified filler.
[0011] Furthermore, the amount of γ-aminopropyltriethoxysilane used in step B1 is 1-2% of the mass of graphene oxide, and the molar ratio of γ-aminopropyltriethoxysilane to dicyclohexylcarbodiimide is 1:1.
[0012] Furthermore, the amount ratio of the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step B2 is 1g:8mL:10mL:10mL:1mL:20mL, and the mass fraction of the hydrochloric acid solution is 5%.
[0013] Beneficial effects of the present invention: A highly water-absorbent chenille mat prepared by the present invention comprises weaving chenille yarn, polyester monofilament and modified fiber into yarn to obtain a woven yarn, weaving the woven yarn into a chenille base cloth through a tufting loom, soaking the chenille base cloth in a hexahydrate zinc sulfate aqueous solution, taking it out and drying it, and then dyeing, finishing, repairing and re-bottoming it to obtain the chenille base cloth; the modified fiber is made of acryloyl chloride and p-hydroxybenzaldehyde as raw materials, and the acyl chloride group on the acryloyl chloride reacts with the hydroxyl group on the p-hydroxybenzaldehyde under the action of triethylamine to obtain an intermediate 1 , reacting the intermediate 1 with o-phenylenediamine, so that the aldehyde group on the intermediate 1 reacts with the diamino group on the o-phenylenediamine to form an imidazole group, and subjecting sodium carboxymethyl cellulose, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine and a modified monomer to free radical graft copolymerization under the action of potassium persulfate to obtain a polymer solution, and uniformly blending the polymer solution and the modified filler to obtain a spinning solution, and then electrospinning to obtain a modified fiber, wherein the modified filler uses graphene oxide as a raw material, and under the action of dicyclohexylcarbodiimide, graphene oxide is The carboxyl group on the olefin and the amino group on the γ-aminopropyltriethoxysilane are dehydrated to obtain pretreated graphene, and the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and tetrabutyl titanate are hydrolyzed and polymerized on the surface of the pretreated graphene to form a titanium-containing organic silicon structure, and then calcined under nitrogen protection to obtain a modified filler. The modified fiber contains a large number of hydrophilic groups on the macromolecular carbon chain skeleton and has a certain three-dimensional network structure that can quickly absorb a large amount of water. The side chain contains zwitterions, which can achieve hydrophilic and oleophobic properties. The modified filler contains titanium dioxide, which can be used for photocatalysis and achieve a bactericidal effect during the drying process of the chenille mat. When the chenille base cloth is immersed in a hexahydrate zinc sulfate solution, the imidazole groups on the modified fiber can complex with zinc ions to form an organic framework of zinc, which can further enhance the photocatalytic effect and be embedded between the chenille yarn, polyester monofilament and the modified fiber, thereby enhancing the mechanical properties of the chenille mat. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0015] A production process of a highly absorbent chenille floor mat, comprising the following steps: Chenille yarn, polyester monofilament and modified fiber are woven into yarn to obtain woven yarn, which is woven into chenille base cloth through a tufting loom, and the chenille base cloth is soaked in a hexahydrate zinc sulfate aqueous solution at a temperature of 50°C for 6 hours, taken out and dried, and then dyed, sorted, repaired and re-bottomed to obtain a highly absorbent chenille floor mat.
[0016] The single yarn quantity ratio of the chenille yarn, the polyester monofilament and the modified fiber is 4:1:2.
[0017] The modified fiber is prepared by the following steps: Step A1: Acryloyl chloride, p-hydroxybenzaldehyde, triethylamine and DMF are mixed, and reacted for 2 hours at a speed of 150 r / min and a temperature of 25° C. to obtain intermediate 1; intermediate 1, o-phenylenediamine, potassium carbonate and anhydrous ethanol are uniformly mixed, and refluxed for 10 hours at a speed of 150 r / min and a temperature of 78° C., and the pH value is adjusted to 5 to obtain a modified monomer; Step A2: dissolving sodium carboxymethyl cellulose in deionized water, adding sodium hydroxide solution, stirring and adding acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF at a speed of 120 r / min, a temperature of 70° C. and nitrogen protection, stirring for 10 minutes, adding potassium persulfate, and reacting for 6 hours to obtain a polymer solution; Step A3: The polymer solution and the modified filler are mixed evenly to obtain a spinning solution, and electrospinning is performed under the conditions of a voltage of 20 kV, a spacing of 20 cm, and a speed of 1.5 mL / h to obtain modified fibers.
[0018] The usage ratio of acryloyl chloride, p-hydroxybenzaldehyde and triethylamine in step A1 is 1:1:1.1, and the molar ratio of intermediate 1, o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0019] The amount ratio of sodium carboxymethyl cellulose, deionized water, sodium hydroxide solution, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF described in step A2 is 4.5g:50mL:20mL:20g:8g:15g:60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount of potassium persulfate is 1% by mass of acrylic acid.
[0020] The amount ratio of the polymer solution and the modified filler described in step A3 is 200mL:1g.
[0021] The modified filler is prepared by the following steps: Step B1: dispersing graphene oxide in anhydrous ethanol, stirring and adding γ-aminopropyltriethoxysilane and dicyclohexylcarbodiimide at a speed of 120 r / min and a temperature of 40° C., and reacting for 3 hours to obtain pretreated graphene; Step B2: Mix the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and anhydrous ethanol evenly, stir and add deionized water and hydrochloric acid solution at a speed of 60r / min and a temperature of 65°C, react for 2h, add tetrabutyl titanate, continue to react for 3h, heat to 120°C, keep warm for 1h to obtain a precursor, add the precursor into a muffle furnace, and calcine for 2h at a temperature of 500°C in a nitrogen protection atmosphere to obtain a modified filler.
[0022] The amount of γ-aminopropyltriethoxysilane used in step B1 is 1% by mass of graphene oxide, and the molar ratio of γ-aminopropyltriethoxysilane to dicyclohexylcarbodiimide is 1:1.
[0023] The amount ratio of the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step B2 is 1g:8mL:10mL:10mL:1mL:20mL, and the mass fraction of the hydrochloric acid solution is 5%. Example 2
[0024] A production process of a highly absorbent chenille floor mat, comprising the following steps: Chenille yarn, polyester monofilament and modified fiber are woven into yarn to obtain woven yarn, which is woven into chenille base cloth through a tufting loom, and the chenille base cloth is soaked in a hexahydrate zinc sulfate aqueous solution at a temperature of 55°C for 7 hours, taken out and dried, and then dyed, sorted, repaired and re-bottomed to obtain a highly absorbent chenille floor mat.
[0025] The single yarn quantity ratio of the chenille yarn, the polyester monofilament and the modified fiber is 4:1:2.
[0026] The modified fiber is prepared by the following steps: Step A1: Acryloyl chloride, p-hydroxybenzaldehyde, triethylamine and DMF were mixed, and reacted at a speed of 150 r / min and a temperature of 28° C. for 2.5 hours to obtain intermediate 1; intermediate 1, o-phenylenediamine, potassium carbonate and anhydrous ethanol were uniformly mixed, and refluxed at a speed of 150 r / min and a temperature of 80° C. for 13 hours, and the pH value was adjusted to 5 to obtain a modified monomer; Step A2: dissolving sodium carboxymethyl cellulose in deionized water, adding sodium hydroxide solution, stirring and adding acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF at a speed of 120 r / min, a temperature of 73° C. and nitrogen protection, stirring for 15 minutes, adding potassium persulfate, and reacting for 7 hours to obtain a polymer solution; Step A3: The polymer solution and the modified filler are mixed evenly to obtain a spinning solution, and electrospinning is performed under the conditions of a voltage of 20 kV, a spacing of 25 cm, and a speed of 1.5 mL / h to obtain modified fibers.
[0027] The usage ratio of acryloyl chloride, p-hydroxybenzaldehyde and triethylamine in step A1 is 1:1:1.1, and the molar ratio of intermediate 1, o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0028] The amount ratio of sodium carboxymethyl cellulose, deionized water, sodium hydroxide solution, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF described in step A2 is 4.5g:50mL:20mL:20g:8g:15g:60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount of potassium persulfate is 1% by mass of acrylic acid.
[0029] The amount ratio of the polymer solution and the modified filler described in step A3 is 200mL:3g.
[0030] The modified filler is prepared by the following steps: Step B1: dispersing graphene oxide in anhydrous ethanol, stirring and adding γ-aminopropyltriethoxysilane and dicyclohexylcarbodiimide at a speed of 120 r / min and a temperature of 45° C., and reacting for 4 hours to obtain pretreated graphene; Step B2: The pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and anhydrous ethanol were mixed evenly, stirred and deionized water and hydrochloric acid solution were added at a speed of 60 r / min and a temperature of 68°C, and the reaction was carried out for 3 hours. Then, tetrabutyl titanate was added and the reaction was continued for 3 hours. The temperature was raised to 125°C and kept warm for 1.5 hours to obtain a precursor. The precursor was added into a muffle furnace and calcined for 3 hours at a temperature of 530°C in a nitrogen protection atmosphere to obtain a modified filler.
[0031] The amount of γ-aminopropyltriethoxysilane used in step B1 is 1-2% of the mass of graphene oxide, and the molar ratio of γ-aminopropyltriethoxysilane to dicyclohexylcarbodiimide is 1:1.
[0032] The amount ratio of the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step B2 is 1g:8mL:10mL:10mL:1mL:20mL, and the mass fraction of the hydrochloric acid solution is 5%. Example 3
[0033] A production process of a highly absorbent chenille floor mat, comprising the following steps: Chenille yarn, polyester monofilament and modified fiber are woven into yarn to obtain woven yarn, which is woven into chenille base cloth through a tufting loom, and the chenille base cloth is soaked in a hexahydrate zinc sulfate aqueous solution at a temperature of 60°C for 8 hours, taken out and dried, and then dyed, sorted, repaired and re-bottomed to obtain a highly absorbent chenille floor mat.
[0034] The single yarn quantity ratio of the chenille yarn, the polyester monofilament and the modified fiber is 4:1:2.
[0035] The modified fiber is prepared by the following steps: Step A1: Acryloyl chloride, p-hydroxybenzaldehyde, triethylamine and DMF are mixed, and reacted at a speed of 200 r / min and a temperature of 30° C. for 3 h to obtain intermediate 1; intermediate 1, o-phenylenediamine, potassium carbonate and anhydrous ethanol are uniformly mixed, and refluxed at a speed of 200 r / min and a temperature of 80° C. for 15 h, and the pH value is adjusted to 5.5 to obtain a modified monomer; Step A2: dissolving sodium carboxymethyl cellulose in deionized water, adding sodium hydroxide solution, stirring and adding acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF at a speed of 150 r / min, a temperature of 75° C. and nitrogen protection, stirring for 15 minutes, adding potassium persulfate, and reacting for 8 hours to obtain a polymer solution; Step A3: The polymer solution and the modified filler are mixed evenly to obtain a spinning solution, and electrospinning is performed under the conditions of a voltage of 25 kV, a spacing of 25 cm, and a speed of 1.5 mL / h to obtain modified fibers.
[0036] The usage ratio of acryloyl chloride, p-hydroxybenzaldehyde and triethylamine in step A1 is 1:1:1.1, and the molar ratio of intermediate 1, o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0037] The amount ratio of sodium carboxymethyl cellulose, deionized water, sodium hydroxide solution, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF described in step A2 is 4.5g:50mL:20mL:20g:8g:15g:60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount of potassium persulfate is 1% by mass of acrylic acid.
[0038] The amount ratio of the polymer solution and the modified filler described in step A3 is 200mL:5g.
[0039] The modified filler is prepared by the following steps: Step B1: dispersing graphene oxide in anhydrous ethanol, stirring and adding γ-aminopropyltriethoxysilane and dicyclohexylcarbodiimide at a speed of 150 r / min and a temperature of 50° C., and reacting for 5 hours to obtain pretreated graphene; Step B2: The pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and anhydrous ethanol were mixed evenly, stirred and deionized water and hydrochloric acid solution were added at a speed of 80 r / min and a temperature of 70°C, and the reaction was carried out for 3 hours. Then, tetrabutyl titanate was added and the reaction was continued for 5 hours. The temperature was raised to 130°C and kept warm for 1.5 hours to obtain a precursor. The precursor was added into a muffle furnace and calcined for 3 hours at a temperature of 550°C in a nitrogen protection atmosphere to obtain a modified filler.
[0040] The amount of γ-aminopropyltriethoxysilane used in step B1 is 2% by mass of graphene oxide, and the molar ratio of γ-aminopropyltriethoxysilane to dicyclohexylcarbodiimide is 1:1.
[0041] The amount ratio of the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step B2 is 1g:8mL:10mL:10mL:1mL:20mL, and the mass fraction of the hydrochloric acid solution is 5%.
[0042] Comparative Example 1 Compared with Example 1, no modified filler was added in this comparative example, and the remaining steps were the same.
[0043] Comparative Example 2 Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.
[0044] Comparative Example 3 Compared with Example 1, this comparative example did not add 2-methacryloyloxyethyl phosphorylcholine, and the remaining steps were the same.
[0045] The braided yarns obtained in Examples 1-3 and Comparative Examples 1-3 were tested for breaking strength according to the standard of GB / T14344-2008 at a pre-tension of 0.2 cN / tex, a clamping distance of 250 mm, and a tensile speed of 250 mm / min. The chenille floor mats were cut into 10 cm×10 cm samples according to the standard of GB / T21655.1-2008, and the chenille floor mats were cut into samples with a size of 2.5 cm×2.5 cm according to the standard of FZ / T 73023-2006, and the number of chenille piles in each sample was ensured to be the same. The antibacterial properties were determined by the oscillation method, and the test strains were Staphylococcus aureus, Escherichia coli, and Candida albicans. The samples were washed 50 times under the same conditions. The test results are shown in the following table;
[0046] It can be seen from the above table that the chenille floor mat prepared in the present application has good mechanical strength, water absorption effect and antibacterial effect.
[0047] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process for a highly absorbent chenille floor mat, characterized in that: The specific steps include: The chenille yarn, polyester monofilament and modified fiber are knitted into yarn to obtain knitted yarn, the knitted yarn is knitted into chenille base cloth, the chenille base cloth is soaked in a hexahydrate zinc sulfate aqueous solution, taken out and dried after soaking, and then dyed, sorted, repaired and backed to obtain a highly absorbent chenille floor mat; The modified fiber is prepared by the following steps: Step A1: acryloyl chloride, p-hydroxybenzaldehyde, triethylamine and DMF are mixed to react to obtain intermediate 1, intermediate 1, o-phenylenediamine, potassium carbonate and anhydrous ethanol are mixed and refluxed to react, and the pH value is adjusted to be acidic to obtain a modified monomer; Step A2: dissolving sodium carboxymethyl cellulose in deionized water, adding sodium hydroxide solution, stirring and adding acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF, stirring, adding potassium persulfate, reacting, and preparing a polymer solution; Step A3: spinning the polymer solution and the modified filler to obtain modified fibers; The modified filler is prepared by the following steps: Step B1: dispersing graphene oxide in anhydrous ethanol, stirring and adding γ-aminopropyltriethoxysilane and dicyclohexylcarbodiimide to react to obtain pretreated graphene; Step B2: pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane and anhydrous ethanol are mixed and stirred, and deionized water and hydrochloric acid solution are added. After the reaction, tetrabutyl titanate is added and the reaction is continued to obtain a precursor. The precursor is calcined to obtain a modified filler.
2. The production process of a highly absorbent chenille floor mat according to claim 1, characterized in that: The usage ratio of acryloyl chloride, p-hydroxybenzaldehyde and triethylamine in step A1 is 1:1:1.1, and the molar ratio of intermediate 1, o-phenylenediamine and potassium carbonate is 1:1.1:1.
5.
3. The production process of a highly absorbent chenille floor mat according to claim 1, characterized in that: The amount ratio of sodium carboxymethyl cellulose, deionized water, sodium hydroxide solution, acrylic acid, 2-methacryloyloxyethyl phosphorylcholine, modified monomer and DMF described in step A2 is 4.5g:50mL:20mL:20g:8g:15g:60mL.
4. The production process of a highly absorbent chenille floor mat according to claim 1, characterized in that: The amount ratio of the polymer solution and the modified filler described in step A3 is 200mL:1-5g.
5. The production process of a highly absorbent chenille floor mat according to claim 1, characterized in that: The amount of γ-aminopropyltriethoxysilane used in step B1 is 1-2% of the mass of graphene oxide, and the molar ratio of γ-aminopropyltriethoxysilane to dicyclohexylcarbodiimide is 1:
1.
6. The production process of a highly absorbent chenille floor mat according to claim 1, characterized in that: The amount ratio of the pretreated graphene, methyltriethoxysilane, dimethyldiethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step B2 is 1g:8mL:10mL:10mL:1mL:20mL.
7. A highly absorbent chenille floor mat, characterized in that: Prepared according to any one of the production processes described in claims 1-6.
Citation Information
Patent Citations
Preparation method of super water-absorbent true color short hair chenille mat
CN108301244A
Long-acting antibacterial polyvinyl acetal sponge and preparation method thereof
CN116574300A
High-toughness polymer medical catheter and preparation method thereof
CN117731844A
Novel wear-resistant leather and preparation process thereof
CN118404876A
Chenille waterproof floor mat and production process thereof
CN119287596A